Hasya Najihah receives Academic Excellence Award from the Pahang Islamic Religious and Malay Customs Council (MUIP) - Hafizatulazlin, Abdul Aziz (UMPSA, 2024)
GAMBANG, 26 October 2024 – Hasya Najihah Mohd Ghazali, 21, who achieved a Cumulative Grade Point Average (CGPA) of 3.23, did not expect to receive the Academic Excellence Award from the Pahang Islamic Religious and Malay Customs Council (MUIP), presented by the Pro-Chancellor of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), Tan Sri Dato’ Sri (Dr.) Abi Musa Asa’ari, during the Second Session of the 19th UMPSA Convocation Ceremony.